1992
DOI: 10.1111/j.1365-2249.1992.tb06483.x
|View full text |Cite
|
Sign up to set email alerts
|

A model for the investigation of factors influencing haemorrhagic necrosis mediated by tumour necrosis factor in tissue sites primed with mycobacterial antigen preparations

Abstract: SUMMARYMycobacterial lesions and skin sites challenged with soluble mycobacterial antigen are very sensitive to the necrotizing effect of tumour necrosis factor (TNE). We have used a model that permits separate quantitative assessment of swelling and haemorrhage to show that when these reactions are elicited in mice that have not been deliberately immunized, pretreatment of the mice with lipopolysaccharide (LPS), or with a MoAb to CR3 which blocks emigration of myeloid cells into the tissues, will block both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 22 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…For a long time, IN has been linked to DTH (considered as an independent form of cellular immunity), essentially as a mechanism to destroy macrophages that are poorly activated by cellular-mediated immunity and thus harbor living bacilli [1,2] or as a cytotoxic activity mostly mediated by CD8 þ cells [20]. Another perspective was given by suggesting that the origin of IN was a local type of Shwartzman reaction [5] and that TNF plays a key role in the development of IN based on the evidence obtained using an experimental model of skin lesions in foot pads [4], which also showed that a Th2 environment would favor such a necrosis [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a long time, IN has been linked to DTH (considered as an independent form of cellular immunity), essentially as a mechanism to destroy macrophages that are poorly activated by cellular-mediated immunity and thus harbor living bacilli [1,2] or as a cytotoxic activity mostly mediated by CD8 þ cells [20]. Another perspective was given by suggesting that the origin of IN was a local type of Shwartzman reaction [5] and that TNF plays a key role in the development of IN based on the evidence obtained using an experimental model of skin lesions in foot pads [4], which also showed that a Th2 environment would favor such a necrosis [21].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, infected granulomas were considered to be ''prepared'' sites because of the presence of M. tuberculosis. The release of tumor necrosis factor (TNF) from macrophages activated and triggered in the lesion may cause tissue damage [4,5].…”
Section: Introductionmentioning
confidence: 99%